A internacionalização da economia e seus reflexos na responsabilidade civil dos administradores das sociedades anônimas - Oliveira, Shirley Meschke Mendes Franklin de (2007)
This dissertation addresses the effects of globalization on the civil liability of directors & officers of joint-stock companies. Starting with the evolution of capitalization until the consolidation of a new world economic order, this work elaborates on one of the most relevant effects of the latest developments in international trade: the competition among domestic and international companies. Within this context, the pursuit of new markets by global companies and their concern with investment costs have stood out. Going public as a means of surviving fierce competition is analyzed, followed by an overview of the capital market and its recent growth. To that end, the evolution of the capital market and of companies is given due consideration. It is thus shown that investors and stakeholders have become increasingly knowledgeable and demanding in terms of greater business security and transparency. This growing awareness has evolved into the so-called corporate governance, which instituted duties, obligations and above all the liability of directors & officers. As this dissertation develops, it will also focus on the duties of directors & officers and on the evolution of civil liability, always demonstrating that legal changes have come in the sway of the globalization of economies